2010
DOI: 10.1007/s11947-009-0315-7
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Physico-Chemical, Microbial and Sensory Properties of Sweetener/Sweetener Blends in Lassi During Storage

Abstract: Storage studies of artificially sweetened lassi samples revealed that the binary sweetener aspartame × acesulfame-k blend (0.05% equivalence, 50:50, 0.05%*) was the best blend as it resembled control in all the sensory attributes up to 5 days of storage. Increase in acidity and viscosity and decrease in pH of artificially sweetened lassi samples was similar to control lassi during storage and was not influenced by the addition of sweetener/sweetener blends. The decrease in lactic and increase in yeast and mold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The discovery of a large number of sweeteners during the last decade has triggered the development of new sugar free products, particularly for diabetics, people on special diets and/or for the obese. Several artificial sweeteners incorporated low calorie products like low calorie flavoured milk (Arora et al 2001(Arora et al , 2008Bhardwaj et al 2009), burfi (Arora et al 2010), kalakand (Arora et al 2008), lassi (George et al 2012), dietetic chhana kheer (Gautam et al 2012) and lal peda (Jain et al 2012) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of a large number of sweeteners during the last decade has triggered the development of new sugar free products, particularly for diabetics, people on special diets and/or for the obese. Several artificial sweeteners incorporated low calorie products like low calorie flavoured milk (Arora et al 2001(Arora et al , 2008Bhardwaj et al 2009), burfi (Arora et al 2010), kalakand (Arora et al 2008), lassi (George et al 2012), dietetic chhana kheer (Gautam et al 2012) and lal peda (Jain et al 2012) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Being aware of the impact of sugar on health, today's health conscious consumer is looking for the low-sugar or sugar-free Indian traditional dairy products. With a view to provide the pleasure of ethnic Indian dairy delicacies to people on restricted diet, attempts have been made to develop various artificially sweetened products such as burfi (Arora et al, 2007Prabha, 2006), gulabjamun (Chetana, Manohar, & Reddy, 2004), rasogolla, kulfi (Garg, 2005) and lassi (George, Arora, Sharma, Wadhwa, & Singh, 2010;Khurana, 2006). About 9% of the total milk produced in India is converted into fermented milk products (Singh, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The multiple‐sweetener approach involving use of binary blend resulted in 38% reduction in usage level when compared with single sweetener aspartame. There was about 46% reduction in calorific value of artificially sweetened lassi when compared with that of control lassi (George et al. 2010a,b).…”
Section: Introductionmentioning
confidence: 90%